Pengaruh Kualitas Produk Dan Harga Terhadap Minat Beli Produk Kecantikan Ms Glow Pada Penduduk Perempuan Di Kabupaten Karawang - Fida Nur Auliya Anwar; Novian Ekawati (STIE AMKOP, 2022)
The purpose of this study is to find out and explain the description of product quality, price and buying interest in MS GLOW beauty products. To find out and analyze the partial effect of product quality and price on buying interest in MS GLOW beauty products. To know and analyze the simultaneous effect of product quality and price on buying interest in MS beauty products. GLOW. This research method uses descriptive and verification methods with a quantitative approach. The sample in this study was 100 samples using the propotionate stratified random sampling technique, the data collection technique used using a Likeert scale. The data analysis technique used is path analysis. The results of this study are that there is a partial effect of product quality on buying interest of 45.1%, there is a partial effect of price on buying interest of 17.3%. Simultaneously product quality and price have a significant influence on buying interest. Keywords: Product Quality, Price, Buying Interest